Automation of pulmonary functional tests - Prieto H., F.; Mendoza E., P.; Olvera L., T.; Cicero S., R, (Revista Mexicana de Ingenieria Biomedica, 1988)
Through a personal computer and an analog / digital converter, we installed an automatic system to capture data, perform calculations and write the report in a pulmonary functional testing laboratory.